Analysis Of Delay Factors And Construction Claims Of Apartments And Commercial Building - Jonbi; Azaria Andreas; Resti Nur Arini; Marlay Yuze (Jurnal Infrastruktur, 2020)
The implementation of construction it is often found inaccuracies in both time and cost between planning and the conditions of implementation on the site. This will result in delays in the execution of the work. In the end there will be a decrease in terms of quality and delay in completion of work. This research aims to analyze the factors causing delays in a building construction project, and identify claims that can be compensated for additional time and costs by the owner. This case studies of this research is analyzing delay in building project, and then the data will be analyzed using the Relative Important Index (RII) approach to obtain the factors with the highest value. Source of respondents chosen is limited from those who have experience in the field of building construction projects. The results shows the indicate of the delay in the implementation of the most important projects caused by late payment by the project owner (owner). In this study, the potential for delays in a construction project caused by the owner reaches 60% while by the contractor by 30%, the rest by force majeure.